Purification and characterization of a T-antigen specific lectin from the coelomic fluid of a marine invertebrate, sea cucumber (Holothuria scabra) - Gowda, Nagaraj M.; Goswami, Usha; Khan, Mohammad Islam (Fish & Shellfish Immunology, 2008)
A novel lectin was purified from the coelomic fluid of the sea cucumber Holothuria scabra (HSL), subjected to bacterial challenge. HSL is a monomeric glycoprotein of molecular mass 182 kDa. The lectin is highly thermostable as it retains full activity for 1 h at 80 degrees C. Further, the hemagglutination activity of HSL is unaffected by pH in the range 2-11. Unlike other lectins purified from marine invertebrates, the hemagglutination activity of HSL does not require any divalent metal ions. The affinity profile of HSL was studied by a combination of hemagglutination inhibition and fluorescence spectroscopy. HSL binds to desialylated glycoproteins, Me alpha Gal, T-antigen and T (alpha-ser)-antigen with a distinction between beta 1-4 and beta 1-3 linkages. Me alpha-T-antigen was a potent ligand having highest affinity (K-a 8.32 x 10(7) M-1). Monosaccharide binding is enthalphically driven while disaccharide binding involves both entropic and enthalpic contributions. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Fluorescence spectroscopy; Holothuria scabra; Lectin; marine invertebrate; Thermodynamic properties